Subjective global assessment for nutritional assessment of hospitalized patients requiring haemodialysis: A prospective cohort study. Issue 11 (11th October 2016) - Tan, Sheau Kang; Loh, Yet Hua; Choong, Hui Lin; Suhail, Sufi M
Abstract: Aim: Evidence has validated that the nutritional status of hospitalized patients on haemodialysis could be compromised because of admission‐related and hospital‐associated morbidities on the background of their kidney disease. However, nutritional status is not assessed and monitored routinely during the hospitalization period. The aim of the present study was to assess the nutritional status of hospitalized patients requiring haemodialysis with the subjective global assessment (SGA) tool during the hospitalization period. Methods: This is a prospective cohort study conducted in an acute tertiary general hospital. Patients aged 21–75 years old, admitted for various illnesses and requiring haemodialysis between November 2011 and May 2012 were enrolled into this study. A trained dietician assessed patients' nutritional status with the SGA tool, which included historical data on weight change, dietary intake, gastrointestinal symptoms, functional capacity, comorbidities and physical examination on subcutaneous fat loss, muscle wasting and presence of oedema and/or ascites. Patients were categorized under three groups: SGA‐A (well‐nourished), SGA‐B (moderately malnourished) and SGA‐C (severely malnourished). Results: Eighty patients (mean ± SD age = 59 ± 10 years; 76% Chinese ethnicity) were assessed. Mean ± SD body mass index (BMI) was 25.1 ± 6.1 kg/m 2 . SGA categories were 48% SGA‐A, 46% SGA‐B, and 6% SGA‐C. Mean energy and protein intake ( P  < 0.001), length of hospitalization stay ( P  = 0.03) and BMI ( P  = 0.001) were significantly different across the three categories of nutritional status. Conclusions: More than half of the hospitalized patients requiring haemodialysis were malnourished. It is important to incorporate SGA in the care of hospitalized haemodialysis patients for early detection of malnutrition and for medical nutrition therapy to optimise patients' nutritional status for better outcomes. Summary at a Glance: SGA has been widely applied in the PD population. This study uses SGA in HD patients in an Asian setting and examines its usefulness.